Programa de ejercicios terapéuticos y profilácticos para pacientes con síndrome metabólico del Hospital Público Dr. Publio Escobar Gómez De la Torre del cantón Colta. - Víctor Daniel, Cabrera Santillán (2017)
The objective of the research was to design a program of therapeutic and prophylactic exercises to reduce the waist - hip index in patients with Metabolic Syndrome, which improved the physical conditions and the quality of life of the patients of the Public Hospital Dr. Publio Escobar Gómez de la Torre of Colta, descriptively, the sample of patients with metabolic syndrome presented the following characteristics: 51% women and 49% men, 51% indigenous and 49% mestizos, the population presented ages between 50 and 62 years, showed favorable changes in consumption habits of adult patients. The waist hip index (CCI) decreased in patients after undergoing the program of therapeutic and prophylactic exercises. Finally, the quality of life index of adult patients improved significantly by showing a better psychological, physical state, greater level of independence, better interpersonal, social relationships and a better relationship with their environment. With this program of therapeutic and prophylactic exercises, the risks associated with the metabolic syndrome were reduced in the patients who attended the Colta Hospital, which improved the physical conditions and their quality of life.